Transnational terrorims as a spillover of domestic disputes in other countries - Tony Addison; S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper models transnational terrorism as a three-way strategic interaction involving a government that faces armed opposition at home, which may spill over in the form of acts of terrorism by the state's opponents against the government's external sponsor. The external sponsor also utilizes deterrence against potential terrorists, which only lowers terrorism if terrorists are not intrinsically motivated by a deep-seated sense of humiliation. A rise in the external power's preference for deterrence against terrorism may backfire in these circumstances. Increases in the government's military efficiency against the rebels, who are also terrorists against the government's sponsor raise overall levels of violence. – conflict ; terrorism ; civil war
Keywords: C72; D81; H11; O19; 330; Politische Gewalt; Theorie; Nichtkooperatives Spiel